The use of tricyclic antidepressants in the treatment of fibromyalgia: a literature review (Research, Society and Development, 2022)
Introduction: Tricyclic antidepressants (TCAs) are widely used as analgesics for chronic low back pain and neuropathic pain. Antidepressants do not significantly influence the normal organism in its basal state, they only correct anomalous conditions. Antidepressants with different chemical structures have in common the ability to acutely increase the synaptic availability of one or more neurotransmitters, through action on several specific receptors and enzymes. Objective: The objective of this work is to demonstrate the mechanism of action of antidepressants and their reactions. Methodology: the research was developed through searches on the Scielo (Electronic Library Scientifc Electronic Library Online) and Google academic platforms. Based on a literature review, according to Cunha, Cunha & Alves, (2014). The following descriptors were used: Fibromyalgia; Tricyclic Antidepressants; Pharmacokinetics. Conclusion: The treatment of fibromyalgia is individualized, and does not propose a cure. The objective is to reduce the suffering of its patients, improve functionality and, as far as possible, personal autonomy and quality of life. Most conducts and recommendations have a lot in common, but they are not totally congruent, showing dynamism and changes as knowledge accumulates on a subject on which consensus is still far from occurring.